High-performance metal injection titanium alloy feed and preparation method thereof
By adding Fe and rare earth Y elements to the titanium alloy feed and using wax-based binder, the problem of poor processing performance of titanium alloy is solved, and efficient and low-cost titanium alloy feeding preparation is achieved, and the tensile strength and plasticity of the material are improved.
Patent Information
- Application Number
- CN202510070682.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-18
AI Technical Summary
The poor processing performance of titanium alloys leads to low processing efficiency, high material waste and high cost, which limits its application range.
High-performance metal-injected titanium alloy feed is used, which includes a metal powder mixture and a wax-based binder. Through specific ratios and processes, the components segregation during smelting are reduced, the tensile strength is improved, and the phase change point is reduced.
It realizes the reduction of component segregation during smelting, improves tensile strength, reduces phase change points, broadens the alloy processing window, reduces feeding preparation costs, and improves product dimensional accuracy and performance.
Smart Images

Figure CN119634735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloys, and in particular to a high-performance metal injection titanium alloy feed and a preparation method thereof. Background Art
[0002] Titanium and titanium alloys have low density, high specific strength, anti-oxidation, biocompatibility and good corrosion resistance. They have a wide operating temperature range and are high-quality metal structural materials and functional materials. They have been widely used in aerospace, navigation, automobiles, power generation, biomedicine and other fields; but titanium and titanium alloys have high melting points and hardness, poor processing, forming and cutting performance, low efficiency, large material waste and high cost when processed by traditional machining methods; therefore, their application range is subject to certain restrictions. There is a large demand for complex and precise small titanium alloy structural parts, but the processing process is complex and the cost is high. Therefore, it is very important to find a low-cost and high-performance preparation technology for titanium alloy complex structural parts, which will greatly promote the production and application of titanium and titanium alloy complex structural parts.
[0003] Metal Injection Molding (MIM) is a net forming process that combines powder metallurgy technology with plastic injection molding technology. It has the advantages of high raw material utilization, flexible component adjustment, and net forming or near net forming. It can produce highly complex and high-precision parts with a size of less than 100 mm. Most of them are used in medical device structural parts and aerospace fasteners. In this context, Metal Injection Molding (MIM) is an ideal choice for titanium alloy processing. Due to the high cost of titanium alloy raw materials and the decisive role of feeding on the performance of titanium alloy products; therefore, low-cost and high-performance titanium alloy feeding preparation technology is the main problem in its current application and promotion. Summary of the invention
[0004] In order to overcome the deficiencies of the prior art, the present invention provides a high-performance metal injection titanium alloy feedstock and a preparation method thereof which can reduce component segregation during smelting, improve tensile strength, and reduce phase transition point.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is a high-performance metal injection titanium alloy feed, comprising a metal powder mixture and a binder, wherein the ratio of the binder to the metal powder mixture is (1.5-2.5):(7.5-8.5);
[0006] The metal powder mixture includes spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder.
[0007] Preferably, the mass percentages of the components of the metal powder mixture are: 0.1% to 0.2% of spherical reduced iron powder; 0.4% to 0.6% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder.
[0008] Preferably, the binder includes ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin; wherein the mass percentages of the components of the binder are: ethylene-vinyl acetate copolymer 10% to 25%, polypropylene 5% to 10%, stearic acid 3% to 5%, hydrogenated styrene-butadiene block copolymer 8% to 15%, microcrystalline wax 10% to 15%, and paraffin 40% to 60%.
[0009] Preferably, the particle size of the spheroidized titanium alloy powder is 500 mesh, the particle size of the spherical reduced iron powder is 500 mesh, and the particle size of the rare earth metal yttrium powder is 200 mesh.
[0010] Preferably, the ratio of the binder to the metal powder mixture is 2:8.
[0011] Preferably, the mass percentages of the components of the metal powder mixture are: 0.15% of spherical reduced iron powder; 0.5% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder.
[0012] Preferably, the mass percentages of the components of the binder are: 18% ethylene-vinyl acetate copolymer, 7% polypropylene, 4% stearic acid, 10% hydrogenated styrene-butadiene block copolymer, 13% microcrystalline wax, and 48% paraffin wax.
[0013] A method for making a high-performance metal injection titanium alloy feedstock, comprising:
[0014] Batching: obtaining a mixture of a binder and a metal powder, wherein the ratio of the binder to the metal powder mixture is (1.5-2.5):(7.5-8.5);
[0015] Mixing, firstly, adding metal powder into the mixing chamber of the mixer, pressurizing the mixing chamber to keep the pressure in the mixing chamber at 0.3-0.8 MPa; adding argon into the mixing chamber at a rate of 15-25 L / min; heating at 160-200° C. for 20-40 min, then sequentially adding ethylene-vinyl acetate copolymer, polypropylene and hydrogenated styrene-butadiene block copolymer into the mixing chamber, mixing for 20-30 min, then continuously adding stearic acid, microcrystalline wax and paraffin into the mixing chamber, mixing for 25-35 min, and then completing the mixing;
[0016] The mixed materials are granulated, formed, degreased and sintered to obtain feed material.
[0017] Preferably, the binder comprises ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin; wherein the mass percentages of the components of the binder are: ethylene-vinyl acetate copolymer 10% to 25%, polypropylene 5% to 10%, stearic acid 3% to 5%, hydrogenated styrene-butadiene block copolymer 8% to 15%, microcrystalline wax 10% to 15%, paraffin 40% to 60%;
[0018] The metal powder mixture comprises spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder, wherein the mass percentages of the components of the metal powder mixture are: spherical reduced iron powder 0.1% to 0.2%; rare earth metal yttrium powder 0.4% to 0.6%; and the rest is spheroidized titanium alloy powder.
[0019] Preferably, the method for obtaining the metal powder mixture comprises: placing each component of the metal powder mixture into a drum ball mill under argon atmosphere protection conditions for a ball milling time of 1-3 hours, and sieving through a 300-mesh sieve after ball milling to obtain the metal powder mixture.
[0020] The specific beneficial effects of the present invention are:
[0021] 1. By adding Fe to the feed powder, the component segregation during smelting will be reduced, while the tensile strength will be improved, the phase transition point will be reduced, and the alloy processing window will be widened;
[0022] 2. Wax-based binders greatly reduce the preparation cost of feed particles, and have low melting point, good wettability, and good product size accuracy. Melt index: 1200-1800g / cm 3 ;
[0023] 3. Adding trace rare earth Y (yttrium) elements can improve the strength and plasticity of titanium alloys. Although wax-based binders are low-cost and pollution-free, if there is a small amount of carbon in the sample, it will affect the plasticity. However, by adding rare earth elements, Y reacts with the O element in the titanium alloy to generate Y2O3, which not only reduces the oxygen content in the titanium alloy, but also the generated Y2O3 plays a role in refining the grains, thereby improving the plasticity of the material, balancing the contradiction between the strength and toughness of the titanium alloy, and achieving the comprehensive performance requirements of high-strength and high-toughness titanium alloys;
[0024] 4. In the degreasing process, heptane solvent degreasing is first performed and then thermal degreasing is performed, which can greatly reduce the uneven release of internal stress of the material caused by thermal degreasing, thereby affecting the dimensional accuracy and performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiment of the present invention and its design scheme, the following briefly introduces the drawings required for this embodiment. The drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 Metallographic structure photograph of sample A in this example. DETAILED DESCRIPTION
[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present application will be further described in detail below with reference to the accompanying drawings.
[0028] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.
[0029] Example 1
[0030] This embodiment provides a high-performance metal injection titanium alloy feed material, including a metal powder mixture and a binder, wherein the ratio of the binder to the metal powder mixture is (1.5-2.5):(7.5-8.5);
[0031] The binder includes ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin. The mass percentage of each component of the binder is: ethylene-vinyl acetate copolymer 10%-25%, polypropylene 5%-10%, stearic acid 3%-5%, hydrogenated styrene-butadiene block copolymer 8%-15%, microcrystalline wax 10%-15%, paraffin 40%-60%; the use of wax base in the binder greatly reduces the preparation cost of the feed particles, and has low melting point, good wettability, good product size accuracy, and melt index: 1200-1800g / cm 3 .
[0032] The metal powder mixture in this embodiment includes spheroidized titanium alloy powder (Ti-6Al-4V powder), spherical reduced iron (Fe) powder and rare earth metal yttrium (Y) powder, wherein the mass percentage of each component is: spherical reduced iron powder 0.1% to 0.2%; rare earth metal yttrium powder 0.4% to 0.6%; the rest is spheroidized titanium alloy powder; by adding Fe to the feed powder, the component segregation during smelting will be reduced, while the tensile strength will be improved, the phase transition point will be reduced, and the alloy processing window will be widened; at the same time, adding a trace amount of rare earth Y element can improve the strength and plasticity of the titanium alloy. Because the wax-based binder is low-cost and pollution-free, if there is a small amount of carbon in the sample, it will affect the plasticity. However, by adding rare earth elements, Y reacts with the O element in the titanium alloy to generate Y2O3, which not only reduces the oxygen content in the titanium alloy, but also the generated Y2O3 plays a role in refining the grains, thereby improving the plasticity of the material, balancing the contradiction between the strength and toughness of the titanium alloy, and achieving the comprehensive performance requirements of high-strength and high-toughness titanium alloy.
[0033] In another embodiment, the particle size of the spheroidized titanium alloy powder (Ti-6Al-4V powder) is 500 mesh and the tap density is greater than 2.45 g / cm 3 The particle size of the spherical reduced iron powder is 500 mesh, and the particle size of the rare earth metal yttrium powder is 200 mesh.
[0034] Example 2
[0035] This embodiment provides a method for preparing a high-performance metal injection titanium alloy feedstock, comprising:
[0036] Ingredients: A metal powder mixture consisting of spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder is selected; the mass percentages of the components of the metal powder mixture are: 0.1% of spherical reduced iron powder; 0.4% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder; a binder consisting of ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin is selected, wherein the mass percentages of the components of the binder are: 10% of ethylene-vinyl acetate copolymer, 5% of polypropylene, 3% of stearic acid, 8% of hydrogenated styrene-butadiene block copolymer, 15% of microcrystalline wax and 59% of paraffin; the ratio of the binder to the metal powder mixture in the obtained ingredients is: 1.5:8.5.
[0037] Mixing of metal powder mixture: The spheroidized titanium alloy powder in the prepared metal powder mixture is placed in a drum ball mill, and spherical reduced iron powder and rare earth metal yttrium powder are added, and the ball milling time is 2 hours under argon atmosphere protection to obtain a mixed powder, wherein the particle size of the spheroidized titanium alloy powder and the spherical reduced iron powder after grinding is 500 mesh; the particle size of the rare earth metal yttrium powder is 200 mesh.
[0038] Mixing: Add the mixed metal powder into the mixing chamber of the mixer, pressurize the mixing chamber to keep the pressure in the mixing chamber at 0.3MPa; add argon gas into the mixing chamber at a rate of 15L / min; heat at 160°C for 40min, then add ethylene-vinyl acetate copolymer, polypropylene and hydrogenated styrene-butadiene block copolymer in the mixed binder into the mixing chamber in turn, mix for 30min, continue to add stearic acid, microcrystalline wax and paraffin into the mixing chamber, mix for 35min, and then complete the mixing;
[0039] Granulation: The mixed materials are granulated in an environment with an argon pressure of 0.5 MPa and a temperature of 180° C. The cutting speed during the granulation process is 100 rpm, and the cutting process is cooled with argon to obtain titanium alloy feed particles.
[0040] Injection molding: The obtained titanium alloy feed particles are fed into an injection molding machine for injection molding, wherein the injection temperature is 120°C, to obtain injection sample A;
[0041] Degreasing: The obtained injection sample A was first immersed in heptane at 40 °C for 20 h for solvent degreasing, and then thermally degreased at 450 °C under argon atmosphere;
[0042] Sintering: Place the degreased injection sample A into a vacuum sintering furnace for sintering. The sintering temperature of the sintering furnace is 1200°C and the vacuum degree is 10 -3 Pa, the furnace was stopped and cooled after 2 hours to obtain titanium alloy feed particles A. The metallographic structure of sample A was verified as follows: Figure 1 shown.
[0043] Example 3
[0044] This embodiment provides a method for producing a high-performance metal injection titanium alloy feed material, comprising:
[0045] Ingredients: A metal powder mixture consisting of spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder is selected; the mass percentages of the components of the metal powder mixture are: 0.2% of spherical reduced iron powder; 0.6% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder; a binder consisting of ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin is selected, wherein the mass percentages of the components of the binder are: 25% of ethylene-vinyl acetate copolymer, 10% of polypropylene, 5% of stearic acid, 10% of hydrogenated styrene-butadiene block copolymer, 10% of microcrystalline wax and 40% of paraffin; the ratio of the binder to the metal powder mixture in the obtained ingredients is: 2.5:7.5.
[0046] Mixing of metal powder mixture: The spheroidized titanium alloy powder in the prepared metal powder mixture is placed in a drum ball mill, and spherical reduced iron powder and rare earth metal yttrium powder are added. Under argon atmosphere protection, the ball milling time is 2.5 hours to obtain a mixed powder, wherein the particle size of the spheroidized titanium alloy powder and the spherical reduced iron powder after grinding is 500 mesh; the particle size of the rare earth metal yttrium powder is 200 mesh.
[0047] Mixing: Add the mixed metal powder into the mixing chamber of the mixer, pressurize the mixing chamber to keep the pressure in the mixing chamber at 0.8MPa; add argon gas into the mixing chamber at a rate of 25L / min; heat at 200°C for 40min, then add ethylene-vinyl acetate copolymer, polypropylene and hydrogenated styrene-butadiene block copolymer in the mixed binder into the mixing chamber in turn, mix for 20min, continue to add stearic acid, microcrystalline wax and paraffin into the mixing chamber, mix for 25min, and then complete the mixing;
[0048] Granulation: The mixed materials are granulated in an environment with an argon pressure of 0.5 MPa and a temperature of 180° C. The cutting speed during the granulation process is 100 rpm, and the cutting process is cooled with argon to obtain titanium alloy feed particles.
[0049] Injection molding: The obtained titanium alloy feed particles are fed into an injection molding machine for injection molding, wherein the injection temperature is 150°C, to obtain injection sample B;
[0050] Degreasing: The obtained injection sample B was firstly immersed in heptane at 40°C for 20 h for solvent degreasing, and then thermally degreased at 500°C under argon atmosphere;
[0051] Sintering: Place the degreased injection sample A into a vacuum sintering furnace for sintering. The sintering temperature of the sintering furnace is 1250°C and the vacuum degree is 10 -3 Pa, and then the furnace was stopped and cooled after 2 hours to obtain titanium alloy feed particles B.
[0052] Example 4
[0053] This embodiment provides a method for producing a high-performance metal injection titanium alloy feed material, comprising:
[0054] Ingredients: A metal powder mixture consisting of spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder is selected; the mass percentages of the components of the metal powder mixture are: 0.15% of spherical reduced iron powder; 0.5% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder; a binder consisting of ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin is selected, wherein the mass percentages of the components of the binder are: 18% of ethylene-vinyl acetate copolymer, 7% of polypropylene, 4% of stearic acid, 10% of hydrogenated styrene-butadiene block copolymer, 13% of microcrystalline wax and 48% of paraffin; the ratio of the binder to the metal powder mixture in the obtained ingredients is 2:8.
[0055] Mixing of metal powder mixture: The spheroidized titanium alloy powder in the prepared metal powder mixture is placed in a drum ball mill, and spherical reduced iron powder and rare earth metal yttrium powder are added. Under argon atmosphere protection, the ball milling time is 2.5 hours to obtain a mixed powder, wherein the particle size of the spheroidized titanium alloy powder and the spherical reduced iron powder after grinding is 500 mesh; the particle size of the rare earth metal yttrium powder is 200 mesh.
[0056] Mixing: Add the mixed metal powder into the mixing chamber of the mixer, pressurize the mixing chamber to keep the pressure in the mixing chamber at 0.5MPa; add argon gas into the mixing chamber at a rate of 20L / min; heat at 180°C for 30min, then add ethylene-vinyl acetate copolymer, polypropylene and hydrogenated styrene-butadiene block copolymer in the mixed binder into the mixing chamber in turn, mix for 25min, continue to add stearic acid, microcrystalline wax and paraffin into the mixing chamber, mix for 30min, and then complete the mixing;
[0057] Granulation: The mixed materials are granulated in an environment with an argon pressure of 0.5 MPa and a temperature of 180° C. The cutting speed during the granulation process is 100 rpm, and the cutting process is cooled with argon to obtain titanium alloy feed particles.
[0058] Injection molding: The obtained titanium alloy feed particles are fed into an injection molding machine for injection molding, wherein the injection temperature is 130°C, and an injection sample C is obtained;
[0059] Degreasing: The obtained injection sample C was first immersed in heptane at 40 °C for 20 h for solvent degreasing, and then thermally degreased at 480 °C under argon atmosphere;
[0060] Sintering: Place the degreased injection sample A into a vacuum sintering furnace for sintering. The sintering temperature of the sintering furnace is 1225°C and the vacuum degree is 10 -3 Pa, and then the furnace was stopped and cooled after 2 hours to obtain titanium alloy feed particles B.
[0061] Comparative Example
[0062] Ti-6Al-4V spherical powder, binder: 75% paraffin, 5% stearic acid, 20% polyethylene, the ratio of binder to metal powder is 3:7, the obtained binder and metal powder are put into the mixing chamber of the mixer for mixing, and then the mixed material is granulated, formed, degreased and sintered to obtain sample D.
[0063] This example tests the density and tensile strength of Sample A, Sample B, Sample C obtained from Example 2-Example 4 and Sample D obtained from the comparative example. The test results are shown in the following table:
[0064] sample Density / % Tensile strength / MPa Sample A 97.15% 873 Sample B 97.39% 890 Sample C 97.60 882 Sample D 93.12 805
[0065] According to the above table, it can be seen that the density and tensile strength of samples A, B and C prepared by the embodiments provided in the present disclosure are much higher than those of sample D. Specifically, adding a trace amount of rare earth Y (yttrium) element to samples A, B and C can improve the strength and plasticity of titanium alloys, because although the wax-based binder is low-cost and pollution-free, if there is a small amount of carbon element in the sample, it will affect the plasticity. However, by adding rare earth elements, Y reacts with the O element in the titanium alloy to generate Y2O3, which not only reduces the oxygen content in the titanium alloy, but also the generated Y2O3 plays a role in refining the grains, thereby improving the plasticity of the material, balancing the contradiction between the strength and toughness of the titanium alloy, and achieving the comprehensive performance requirements of high-strength and high-toughness titanium alloys.
[0066] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A high performance metal injection titanium alloy feed, characterized in that: It comprises a metal powder mixture and a binder, wherein the ratio of the binder to the metal powder mixture is (1.5-2.5):(7.5-8.5); The metal powder mixture includes spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder.
2. The high performance metal injection titanium alloy feed according to claim 1, characterized in that: The mass percentages of the components of the metal powder mixture are: 0.1% to 0.2% of spherical reduced iron powder; 0.4% to 0.6% of rare earth metal yttrium powder; and the rest is spheroidized titanium alloy powder.
3. The high performance metal injection titanium alloy feed according to claim 1, characterized in that: The binder comprises ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin; wherein the mass percentages of the components of the binder are: 10% to 25% of ethylene-vinyl acetate copolymer, 5% to 10% of polypropylene, 3% to 5% of stearic acid, 8% to 15% of hydrogenated styrene-butadiene block copolymer, 10% to 15% of microcrystalline wax and 40% to 60% of paraffin.
4. The high performance metal injection titanium alloy feed material according to claim 1, characterized in that: The particle size of the spheroidized titanium alloy powder is 500 meshes, the particle size of the spherical reduced iron powder is 500 meshes, and the particle size of the rare earth metal yttrium powder is 200 meshes.
5. The high performance metal injection titanium alloy feed material according to claim 1, characterized in that: The ratio of the binder to the metal powder mixture is 2:
8.
6. The high performance metal injection titanium alloy feed material according to claim 1, characterized in that: The mass percentages of the components of the metal powder mixture are: 0.15% of spherical reduced iron powder; 0.5% of rare earth metal yttrium powder; and the rest of spheroidized titanium alloy powder.
7. The high performance metal injection titanium alloy feed material according to claim 3, characterized in that: The mass percentages of the components of the binder are: 18% of ethylene-vinyl acetate copolymer, 7% of polypropylene, 4% of stearic acid, 10% of hydrogenated styrene-butadiene block copolymer, 13% of microcrystalline wax, and 48% of paraffin wax.
8. A method for making a high-performance metal injection titanium alloy feed, characterized in that: include: Batching: obtaining a mixture of a binder and a metal powder, wherein the ratio of the binder to the metal powder mixture is (1.5-2.5):(7.5-8.5); Mixing, firstly, adding metal powder into the mixing chamber of the mixer, pressurizing the mixing chamber to keep the pressure in the mixing chamber at 0.3-0.8 MPa; adding argon into the mixing chamber at a rate of 15-25 L / min; heating at 160-200° C. for 20-40 min, then sequentially adding ethylene-vinyl acetate copolymer, polypropylene and hydrogenated styrene-butadiene block copolymer into the mixing chamber, mixing for 20-30 min, then continuously adding stearic acid, microcrystalline wax and paraffin into the mixing chamber, mixing for 25-35 min, and then completing the mixing; The mixed materials are granulated, formed, degreased and sintered to obtain feed material.
9. The method for making a high performance metal injection titanium alloy feedstock according to claim 1, characterized in that: The invention is characterized in that: The binder comprises ethylene-vinyl acetate copolymer, polypropylene, stearic acid, hydrogenated styrene-butadiene block copolymer, microcrystalline wax and paraffin; wherein the mass percentages of the components of the binder are: ethylene-vinyl acetate copolymer 10%-25%, polypropylene 5%-10%, stearic acid 3%-5%, hydrogenated styrene-butadiene block copolymer 8%-15%, microcrystalline wax 10%-15%, paraffin 40%-60%; The metal powder mixture comprises spheroidized titanium alloy powder, spherical reduced iron powder and rare earth metal yttrium powder, wherein the mass percentages of the components of the metal powder mixture are: spherical reduced iron powder 0.1% to 0.2%; rare earth metal yttrium powder 0.4% to 0.6%; and the rest is spheroidized titanium alloy powder.
10. The method for making a high performance metal injection titanium alloy feedstock according to claim 9, characterized in that: The method for obtaining the metal powder mixture comprises: placing each component of the metal powder mixture into a drum ball mill under argon atmosphere protection conditions for a ball milling time of 1-3 hours, and sieving through a 300-mesh screen after ball milling to obtain the metal powder mixture.